Minienxertia de Passiflora edulis Sims f. flavicarpa Deg. em porta-enxertos clonais de Passiflora mucronata Lam. : aspectos morfo-histológicos - Oliari, Layane Segantini (2016)
Brazil is the largest producer of passion fruit, with 838,244 tonnes achieved in 2013 in an area of 57,277 hectares (IBGE, 2013), and the yellow passionflower (Passiflora edulis f. flavicarpa) the most cultivated. However this species is affected by the ground fungus Fusarium oxysporum f. sp. passiflorae causing the total withering of the plants. Among the alternatives to be sought, there is the use of wild species, resistant to certain diseases, such as rootstock. In this sense, P. mucronata species becomes an option as the rootstock yellow passionflower to be resistant to the fungus causing this disease. This study aimed to evaluate histological aspects of grafting region and morphological of grafted seedlings of apexes of shoots of P. edulis f. flavicarpa on P. mucronata using the mini-grafting technique proposed by Alexandre et al. (2013), by grafting mode on top in full and simple english. The characteristics evaluated were: attachment (%), diameter of the graft (GD), diameter of the rootstock (RD), callus formation, starch into the tissue of the graft and rootstock and the influence of fastening material and emerged side shoots of the rootstock, 21 days after mini-grafting. Also anatomy grafting slit 60 days after implementation of mini-grafting was observed. It was found that the Parafilm® tape provides greater percentage of attachment, in the presence of starch graft reserve parenchyma. The cells that have undergone mitosis is of primary graft parenchymal, this being a younger tissue, cells possess their greatest division rate and the modality top wedg is more simple and practical to implement the mini-grafting P. edulis f. flavicarpa on P. mucronata.